Eksperimen Pola Difraksi Berbasis Smartphone Menggunakan Remote Control Televisi (TV) untuk Estimasi Lebar Kisi Compact Disc - Maranressy, Fera Dominggas; Latununuwe, Altje; Akyuwen, Frandy; Huliselan, Estevanus Kristian; Buka, Oktosea (Physikos: Journal of Physics and Physics Education, 2024)
A smartphone-based diffraction pattern experiment using a TV remote control has been successfully designed to estimate the width of a CD grating. This innovative experiment not only provides a hands-on learning experience but also has practical implications for physics education. A smartphone can be used as a screen to record and save diffraction patterns, and a TV remote control can be used as a source of infrared light. CDs can replace gratings, making the experiment efficient and accessible. The determination of the infrared wavelength of the TV remote control using a 300 line/mm grid and a 600 line/mm grid resulted in 946.67 nm and 859.33 nm, respectively. A positive linear relationship was found between the distance from the grid to the screen L and the distance from the centre light to the first light p, where the bigger L, the bigger p. Estimating the CD grating width using the infrared wavelength value of 946.67 nm, it was found that the CD grating width was 1632.19 nm. Furthermore, using a wavelength of 859.33 nm, it was found that the CD lattice width was 1481.68 nm, close to the actual CD lattice width.